COVID-19: The world economy needs a lifeline - but which one? - Dorine Boumans; Sebastian Link; Stefan Sauer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper from Dorine Boumans, Sebastian Link and Stefan Sauer (EconPol Europe, ifo Institute) presents the results of a survey of 1000 economic experts in 110 countries on the economic effects of the COVID-19 pandemic and the effectiveness of different policy measures to combat the crisis for different countries. The results indicate that economies all around the globe are severely hit by the COVID-19 crisis. The experts perceive the reductions in investment to have the strongest impact on their domestic economies. In consequence, the experts expect a severe recession in almost all countries in 2020, followed by a long period of economic recovery. The experts rate emergency liquidity assistance to firms as well as temporary tax deferrals for businesses as the most effective policy measures, but do not regard other responses such as helicopter money or lenient bank supervision as being well suited to combat the crisis.
Keywords: 330; Coronavirus; Wirtschaftskrise; Wirtschaftspolitik; Welt